Introspection of the Etiopathological Mechanisms Underlying Noncarious Cervical Lesions: Analysis of the Different Theories and Their Impact on the Mineralized Structures of the Tooth - Mario Dioguardi; Davide Polverari; Francesca Spirito; Giovanna Iacovelli; Diego Sovereto; Enrica Laneve; Giorgia Apollonia Caloro; Andrea Ballini; Lorenzo Lo Muzio (International Journal of Dentistry)
The noncarious cervical lesions (NCCLs) recognize an etiological framework of onset very different from the carious processes with etiology whose bacteria aggregated in a biofilm play a predominant role, leading in this way to the loss of the mineralized structure of the tooth. The pathological picture of the NCCLs, which manifests itself with a clinical picture of dental wear, differs from caries because it mainly recognizes a series of pathological processes, such as erosion, through the action of generally acidic chemical agents and abrasion, which is basically expressed through repeated mechanical trauma characteristic of tooth brushing. However, in the literature, there is no unanimous agreement in identifying only these two mechanisms, but there are some who propose a more marked role of anomalous occlusal loads, which would be unloaded on some teeth which, in addition to both erosive and abrasive mechanisms, would give rise to abfraction. Therefore, the aim of this review was to collect literature etio-pathological information and discuss the mechanisms underlying NCCLs.